Anterior Cervical Discectomy and Fusion Using an "Oversized" PEEK Cage: Radiological and Clinical Outcome. Issue 1 (April 2016) - El-Sharkawi, Mohammad; Gad, Wael
Introduction: There has been controversial data about the effect of cage size on radiological and clinical outcome of anterior cervical discectomy and fusion (ACDF). Oversized cages have been linked to higher incidence of non-union, adjacent segment disease, and unfavorable clinical outcomes. The aim of this work is to evaluate the effect of an oversized PEEK cage on the radiological and clinical outcomes in ACDF. Patients and Methods: Between January 2012 to July 2014, 57 patients (29 single level, 15 double levels, 8 three levels, 5 four levels) underwent ACDF using a stand-alone oversized PEEK cages. They were 35 males and 22 females with mean age 56 ± 13.5 years. The minimum follow up period is one year. The following parameters were measured preoperatively, postoperatively and at final follow up: cervical lordosis (in degrees), disc height (in mm), motion at operated level (in degrees), radiological ASD (present or not) and VAS for neck pain, VAS for arm pain. All complications were as well recorded. Results: The mean cervical lordosis changed from 25°±5.5 postoperative to 7°±4.5 at final follow up. The mean disc height was 5± 2 mm preop, 7 ± 1.5 mm postop and 6 ± 1 mm at final follow up. Residual motion at operated level was observed at 1 year follow up X-rays in 2 patients (one double level and one 3-level) with average 5°. None of them had neck pain and no revision was required. In the postoperative X-rays, the suprajacent level was always observed to be slightly narrowed; this narrowing gradually diminished during the follow up. Radiological ASD developed in 9 patients (16%), all of them remained to date asymptomatic. The average improvement in VAS for neck pain was 27%±8.5 and the average improvement in VAS for arm pain was 33%±9.5. At the final follow up, fusion was achieved in 55 patients (96%) and clinical outcome was excellent. Radiological loss of the postoperative disc height and cervical lordosis and development of radiological ASD did not correlate to poor clinical outcome. No single case of cage dislodgement was observed in this series. Conclusion: The use of a stand-alone oversized PEEK cage in ACDF seems to minimize the incidence of cage dislodgment even in multiple levels ACDF. Despite some radiological settlement and loss of cervical lordosis, an excellent clinical outcome was maintained.